PENERAPAN PROBLEM BASED LEARNING BERBANTUAN ARTIFICIAL INTELLIGENCE DAN QUIZIZ MATERI SILA PANCASILA KELAS 4 SD - Firly Fazza Amalia; Panca Dewi Purwati (STKIP Subang, 2024)
This study aims to describe the application of AI-assisted PBL models and Quiziz in the material for the application of grade 4 Pancasila precepts at SDN 01 Kriyan and describe learning outcomes based on the application of AI-assisted PBL, interactive learning videos, and Quiziz on the application of grade 4 Pancasila precepts at SDN 01 Kriyan. The method used was qualitative descriptive, with research subjects as many as 20 students. The learning process involves the use of AI interactive videos to deepen understanding of the material and Quizizz as an interactive evaluation tool. The results showed a significant improvement in students' understanding and grades after the application of the technology-assisted PBL model, with most students achieving or exceeding the Minimum Learning Completeness Criteria (KKTP). This research suggests that the integration of AI and other educational technologies in the curriculum can improve students' motivation and learning outcomes, while better preparing them to practice the values of Pancasila in their daily lives.